2018
DOI: 10.1177/1120700018812991
|View full text |Cite
|
Sign up to set email alerts
|

Metal ion trend in patients with metal-on-metal total hip arthroplasty: a 10-year prospective study

Abstract: Introduction: There have been reported adverse reactions in patients with large head metal-on-metal hip arthroplasty, therefore metal particle debris are a cause for concern. The aim of this study was to evaluate the release trend of metal ions and the correlated variables. Methods: 54 patients were prospectively enrolled into the study from 2004 to 2006. All patients had 36-mm metal head, Pinnacle acetabular component, Summit stem and Ultamet CoCr alloy liner (Depuy Inc.), and underwent clinical and radiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Earlier studies have shown that the serum metal ion levels, mainly for chromium ions, remain at moderate to high levels after conversion CoC-THA in the elderly population [34,35]. The return to exceptionally low or unnoticeable levels could take more than 3 years [36], which is in accordance with our follow-up outcomes that serum chromium ion levels remain moderately high in a majority of patients 3 years after conversion.…”
Section: Discussionsupporting
confidence: 91%
“…Earlier studies have shown that the serum metal ion levels, mainly for chromium ions, remain at moderate to high levels after conversion CoC-THA in the elderly population [34,35]. The return to exceptionally low or unnoticeable levels could take more than 3 years [36], which is in accordance with our follow-up outcomes that serum chromium ion levels remain moderately high in a majority of patients 3 years after conversion.…”
Section: Discussionsupporting
confidence: 91%
“…To simplify statistical analysis, patients were stratified according to Cr or Co levels into low; (<2 μg/L), medium; (⩾2 and <7 μg/L) and high-risk; (⩾7 μg/L) for ALTR. 5,15,25 At 15-year follow-up the study protocol was implemented and every patient (both symptomatic and nonsymptomatic, irrespectively of ion levels) underwent a hip sonography, an MRI and a CT ( Figure 1). Sonographic results were classified according to Nishii et al, 26 developed as a qualitative screening of the soft tissue findings in MoM THA.…”
Section: Methodsmentioning
confidence: 99%
“…According to our results and previous literature, ALTR develops in the long term, leading to rTHA up to 10-15 years after MoM THA. 12,14,15,38 In the present study, all patients who underwent rTHA for ALTR were symptomatic; the 4 patients revised for ALTR were studied preoperatively with MRI and CT, however not previously with MAVRIC and O-MAR protocols. During surgery only the bearing couple was revised (MoM to CoP), with excision of affected soft tissues.…”
Section: Implant Survivalmentioning
confidence: 99%
See 2 more Smart Citations